The potentiality of bacteriophage on biofilm treatment - Satter, Araf Bin; Samit, Asim Alavi; Rahman, Nayeemur (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.